Stratifying the Presymptomatic Phase of Genetic Frontotemporal Dementia by Serum NfL and pNfH: A Longitudinal Multicentre Study. Issue 1 (29th November 2021) - Wilke, Carlo; Reich, Selina; van Swieten, John C.; Borroni, Barbara; Sanchez‐Valle, Raquel; Moreno, Fermin; Laforce, Robert; Graff, Caroline; Galimberti, Daniela; Rowe, James B.; Masellis, Mario; Tartaglia, Maria C.; et al.
Abstract : Objective: Although the presymptomatic stages of frontotemporal dementia (FTD) provide a unique chance to delay or even prevent neurodegeneration by early intervention, they remain poorly defined. Leveraging a large multicenter cohort of genetic FTD mutation carriers, we provide a biomarker‐based stratification and biomarker cascade of the likely most treatment‐relevant stage within the presymptomatic phase: the conversion stage. Methods: We longitudinally assessed serum levels of neurofilament light (NfL) and phosphorylated neurofilament heavy (pNfH) in the Genetic FTD Initiative (GENFI) cohort (n = 444), using single‐molecule array technique. Subjects comprised 91 symptomatic and 179 presymptomatic subjects with mutations in the FTD genes C9orf72, GRN, or MAPT, and 174 mutation‐negative within‐family controls. Results: In a biomarker cascade, NfL increase preceded the hypothetical clinical onset by 15 years and concurred with brain atrophy onset, whereas pNfH increase started close to clinical onset. The conversion stage was marked by increased NfL, but still normal pNfH levels, while both were increased at the symptomatic stage. Intra‐individual change rates were increased for NfL at the conversion stage and for pNfH at the symptomatic stage, highlighting their respective potential as stage‐dependent dynamic biomarkers within the biomarker cascade. Increased NfL levels and NfL change rates allowed identification of presymptomatic subjects converting to symptomatic disease and capture of proximity‐to‐onset. We estimate stage‐dependent sample sizes for trials aiming to decrease neurofilament levels or change rates. Interpretation: Blood NfL and pNfH provide dynamic stage‐dependent stratification and, potentially, treatment response biomarkers in presymptomatic FTD, allowing demarcation of the conversion stage. The proposed biomarker cascade might pave the way towards a biomarker‐based precision medicine approach to genetic FTD. ANN NEUROL 2022;91:33–47